Faktor-Faktor Yang Mempengaruhi Siswa Dalam Belajar IPS Terpadu Kelas VIII SMP Negri 26 Padang Tahun Ajaran 2013/2014 - Sukma, Artinda - (Pendidikan Sejarah, 2014)
This research of background by problem of result learn students of SMPN 26 that students which not reached KKM, and students still find difficulties in study of IPS Terpadu. This research to the explaining of difficulty faced by studentss in study of IPS Terpadu in class of VIII 8 and VIII 9 SMPN 26, 2013 / 2014.Research type which is used in this research is descriptive reseach, with analysis qualitative , and population of ssample in research is all class students of VIII 8 and 9 in SMPN 26 Padang.With research location in SMPN 26 Padang. Type in this research is primary data, source of data is students of SMPN 26 Padang, passing observation technique, documentation and interview.accuracy of data tested by using data triangulation , of gathered to be data to be analysed with model of interactife which consist of data collecting, data discount, presentation of data and withdrawal of conclusion.